2009
DOI: 10.3126/jnps.v29i2.2040
|View full text |Cite
|
Sign up to set email alerts
|

Maternal Risk Factors and Morbidity Pattern of Very Low Birth Weight Infants: A NICU Based Study at Eastern Nepal

Abstract: Background: Preterm deliveries of babies weighing less than 1500 grams (VLBW, very low birth weight) are of major concern because of maximum perinatal morbidity and mortality found in this group. VLBW babies overload the neonatal intensive care unit (NICU) and their mortality contributes significantly to neonatal and infant mortality. Objectives: To study the common maternal risk factors associated with VLBW births. To study the morbidity and mortality patterns of VLBW babies. Methods: This was a hospital ba… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
19
2

Year Published

2014
2014
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(26 citation statements)
references
References 17 publications
5
19
2
Order By: Relevance
“…NICU based incidence of LBW in the hospital was 28.10%, that of very low birth weight and extremely low birth weight babies were 10.25% and 5.16% respectively which is comparable to other studies. 13,14,15 53% of neonates were males and 47% females which is comparable to the study done by Manikyamba D et al where males were 54.28% and females 45.71%. 14 In other study done by Kayastha S et al males and females were 52.0% and 48.0% respectively 5 .…”
Section: Discussionsupporting
confidence: 79%
See 1 more Smart Citation
“…NICU based incidence of LBW in the hospital was 28.10%, that of very low birth weight and extremely low birth weight babies were 10.25% and 5.16% respectively which is comparable to other studies. 13,14,15 53% of neonates were males and 47% females which is comparable to the study done by Manikyamba D et al where males were 54.28% and females 45.71%. 14 In other study done by Kayastha S et al males and females were 52.0% and 48.0% respectively 5 .…”
Section: Discussionsupporting
confidence: 79%
“…12 Similarly in a study by Poudel P et al major causes of death were HMD (51.0%) and sepsis (34.7%). 13…”
Section: Discussionmentioning
confidence: 99%
“…Seizure Disorder: The current study showed that babies was 25% which is less than the present study but the mortality rate of ELBW was 69.7% which was more than that of the present study [25], babies were more than Poudel et al [26]. There is a wide variety of survival rates reported in various studies [27,28].…”
Section: Pdacontrasting
confidence: 52%
“…12 In a study by Poudel P et al survival rate in VLBW neonates was 54.3%. 13 In a study by Basu S et al mortality rate of 37% was reported in VLBW neonates. 14 In a study by Acharya N et al mortality rate in ELBW and VLBW babies were 69.7% and 25% respectively.…”
Section: Discussionmentioning
confidence: 99%